Pengaruh Earnings Management terhadap Tax Avoidance Sebelum dan Selama Covid-19 pada Perusahaan Manufaktur di Indonesia - Mulyaningsih, Retno; Handayani, Sri (Universitas Proklamasi 45, 2024)
This study aims to examine the effect of earnings management and capital intensity on tax avoidance with sales growth as a moderating variable. This study uses a sample, namely manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The sampling technique used in this study, namely the purposive sampling method with the acquisition of a sampling of 119 samples. The data analysis technique used in this study uses panel data regression and the Chow test to explain the effect of earnings management on tax avoidance before and during Covid-19. This study suggests differences in tax avoidance and earnings management levels in the pandemic era compared to the pre-pandemic era. This study also concludes that earnings management is positively associated with tax avoidance during the pandemic.